A case study of disaster risk reduction governance in Philippine rural higher education: Toward contextualized policy support - Pardillo, Robert S. (Edelweiss Applied Science and Technology, 2025)
This study assesses the implementation of disaster preparedness programs in a rural state university system in the Philippines, in line with the United Nations Sustainable Development Goals (SDGs), particularly SDG 11 (Sustainable Cities and Communities) and SDG 13 (Climate Action). It aims to evaluate preparedness levels and identify factors that influence the resilience of under-resourced higher education institutions. A mixed-methods design was adopted to capture both quantitative indicators and qualitative insights, ensuring a comprehensive understanding of disaster risk reduction efforts in a rural academic setting. This study involved 538 participants across four university campuses. Stratified random sampling was used to select students and faculty, while purposive sampling was applied to DRRM officers, deans, and program chairs. Data were collected using an adapted tool based on the UN International Strategy for Disaster Risk Reduction, and challenges were identified using the Asian Disaster Preparedness Center guidelines. Quantitative data were analyzed using descriptive statistics, Mann-Whitney U, and Kruskal-Wallis H tests. At the same time, qualitative insights from focus group discussions were thematically coded based on Braun and Clarke [1] framework. The results revealed high levels of preparedness in facilities, training, and programs. While no significant differences were found by gender, age, and campus location significantly influenced preparedness levels, with Campus B showing the highest scores. Major challenges included resource limitations, coordination issues, and technical constraints. Despite these, DRRM officers demonstrated a strong commitment to program improvement and innovation. This study contributes to the principles outlined in the Disaster Studies Manifesto by emphasizing the critical role of local institutions in building disaster resilience. It advocates for integrating DRRM into education and governance systems, positioning rural state universities as key actors in promoting community preparedness and sustainable development.